Employees' job satisfaction, organisational commitment and intention to stay at an international hotel in Lesotho - Peete, Mankhabe Blandinah (My University, 2016)
The purpose of this study is to determine the relationship between employees’ job satisfaction (JS), organisational commitment (OC) and intention to stay (ITS) at an international hotel in Lesotho. Employees’ productivity is largely related to their level of job satisfaction. Lumley, Coetzee, Tladinyane and Ferreira (2011:101) are of the view that since job satisfaction involves employees’ motions, it influences an organisation’s well-being with regard to job productivity, employee turnover, absenteeism and life satisfaction Therefore, it is important for an organisation to study the relationships between JS, OC and ITS. A survey questionnaire was devised to collect the information for job satisfaction, organisational commitment and intention to stay from each employee. Two hundred and twenty employees responded to the survey. This study used a quantitative research paradigm and a descriptive research method. Random sampling was deemed appropriate for this study, these choices are motived for in the main study. Participants were asked to complete three test instruments, namely, a Job Satisfaction Survey (JSS), an Organisational Commitment Questionnaire (OCQ) and an Intention to Stay Questionnaire (ITSQ). After analysing the data, the researcher found that there is a relatively strong correlation between job satisfaction, organisational commitment and intention to stay. Generally, higher levels of job satisfaction will lead to higher levels of organisational commitment which in turn will lead to employees staying at organisations. The results indicate that all three variables: JS‚ OC‚ and ITS have positive and significant inter-relationships. Findings and recommendations of this study are important to the management as they indicate the need to develop strategies to deal with the needs of those employees who exhibit low level of organisational commitment. The findings of this study provide valuable insights that can enable the management to create a satisfied and committed workforce
M. Tech. (Business Administration, Faculty of Management Sciences), Vaal University of Technology
Keywords: Job satisfaction; Organisation commitment; Hotel employees; 658.31422; Job satisfaction.; Tourism -- Lesotho